Meta-Analysis for the Prediction of Mortality Rates in a Pediatric Intensive Care Unit Using Different Scores: PRISM-III/IV, PIM-3, and PELOD-2 - Shen, Yaping; Jiang, Juan (Frontiers in Pediatrics, 2021)
Introduction: The risk of mortality is higher in Pediatric Intensive Care Units (PICU). To prevent mortality in critically ill infants, optimal clinical management and risk stratification are required. Aims and objectives: To assess the accuracy of PELOD-2, PIM-3, and PRISM-III/IV scores to predict outcomes in pediatric patients. Results: A total of 29 studies were included for quantitative synthesis in meta-analysis. PRISM-III/IV scoring showed pooled sensitivity of 0.78; 95% CI: 0.72 to 0.83 and pooled specificity of 0.75; 95% CI: 0.68 to 0.81 with 84% discrimination performance (SROC 0.84, 95% CI: 0.80 to 0.87). In case of PIM-3, pooled sensivity 0.75; 95% CI 0.71 to 0.79 and pooled specicifiy 0.76; 95% CI 0.73 to 0.79 were observed with good dicriminaition power (SROC, 0.82, 95% CI 0.78 to 0.85). PELOD-2 scoring system had pooled sensitivity of 0.78(95% CI: 0.71 to 0.83) and combined specificity of 0.75 (95% CI: 0.68 to 0.81), as well as good discriminating ability (SROC 0.83, 95% CI: 0.80 to 0.86) for mortality prediction in PICU patients. Conclusion: PRISM- III/IV, PIM-3 and PELOD-2 had good performance for mortality prediction in PICU but with low to moderate certainty of evidence. More well-designed studies are needed for the validation of the study results.